Effects of Stock Market Liberalisation: Pros and Cons The Difference between Developed and Developing Countries - Visitkijakarn, Vanvarang (2010)
The stock market liberalisation has its own unique effects on an economy as this concept is differentiated from capital account liberalisation and integrating stock market. Earlier study has emphasized on effect of capital account liberalisation on various developing and emerging economies but there has been a scarcity of research on stock market liberalisation and volatility of markets throughout a financial crisis. This study expands on the earlier pool of research by aiming on studying the unique impacts of stock market liberalisation on stock market volatility, foreign direct investment, cost of capital and economic growth. This research attempts to study the changes in stock market volatility over the period 2000-2010, by estimating the stock market volatility of fourteen economies relative to S&P 500 index. The results suggest a tendency for market volatility to revert towards the S&P 500 index for the liberalised economies. Stock market volatility on all the markets with a beta of less than one has increased post liberalisation, while volatility for the markets with a beta higher than one has decreased during the same period. This provides a strong evidence for integration of both developed and developing markets after stock market liberalisation. This research also suggests that capital account control may keep the stock market volatility low for short to medium-term. However, in the long-run stock market liberalisation leads to similar results compared to other developing economies that capital controls have not been used. Finally, the objective of this study is to extend existing literature and to study the volatility of liberalised equity markets prior to and following the recent financial crisis.